A simplified method for quantifying the progressive collapse fragility of multi-story RC frames in China. (January 2023) - Chen, Zefan; Zhu, Yaqiong; Lu, Xinzheng; Lin, Kaiqi
Highlights: A simplified progressive collapse fragility analysis methodology is proposed. The progressive collapse fragility of typical RC frames in China is evaluated. The effects of seismic design intensity and other design conditions are evaluated. The influences of the removed column locations on the resistance are discussed. The most vulnerable components in different RC frames are determined. Abstract: Multi-story reinforced concrete (RC) frames are one of the most widely-used structural systems in engineering practice. To prevent the progressive collapse of RC frames under disastrous events, it is desirable to systematically investigate the progressive collapse fragility of the structures under column loss scenarios. This study proposed a simplified procedure for quantifying the progressive collapse fragility of multi-story RC frames, taking into consideration the influences of dynamic effects and parameter uncertainties. Nine typical RC frames were designed according to the Chinese building codes and investigated by the proposed method. The effects of seismic design intensity and the number of stories on the progressive collapse fragility of the RC frames were investigated. The results indicate that the progressive collapse resistance of multi-story RC frames depends on the combining effects of the structural loads and the bearing capacity of the beams. The structural resistance generally improves when increasing the number of stories. In contrast, it improves with the increase of seismic design intensity only when the seismic load is involved in the controlled load combination. For the RC frames that have various componential dimensions along the height, the stories with a changed componential dimension tend to collapse more likely under column removal scenarios. The outcomes of this study can provide references for quantifying the progressive collapse resistance and recommending appropriate load increase factors for the engineering design of multi-story RC frames in China.